Perception of Herbal Medicine in the Management of Ocular Hypertension: A Case Study of Egor Local Government Area, Edo State - Odjimogho, Stella E.; Ogbeide, Faith Osemudiamen; Odjimogho, Sunny E.; Gabriel, Benjamin O. (Darul Yasin Al Sys, 2025)
Traditional medicine is “the knowledge, skills and practices based on the theories, beliefs and experiences indigenous to different cultures. This study was to determine the perception of preference for traditional medicine to modern medicine in the management of ocular problems amongst adults aged between 18-80 years, in Egor local government area, Benin city. A cross- sectional study was conducted on adults residing in Egor local government area, Benin city with the use of an interview-based questionnaire. The results of this study showed that 39 representing 16.9% of the respondents in the study population used traditional medicine while 180 representing 77.9% without the use of traditional medicine. However, there was no statistically difference between the socio-demographic variables and the use of traditional eye medicines (P>0.05). In conclusion, this study will help clinicians to gain knowledge on the reasons for preference of traditional medicine to orthodox medicine in the treatment of eye problems. It would enable Eye care practitioners increase advocacy on the possible consequences of their choices in order to help the people make informed decisions. It is therefore recommended there should be public enlightenment on the possibility of adverse effects in traditional medicine for the management of ocular problems.